USING EVAPORATIVE COOLING AND PACKAGING TO STORE GREEN PEPPER: USING EVAPORATIVE COOLING AND PACKAGING TO STORE GREEN PEPPER (Iraqi Journal of Market Research and Consumer Protection, 2026)
Green bell peppers, a staple in kitchens worldwide, are notorious for their short shelf life. Fortunately, a simple technology of an evaporative cooling system can offer a promising solution to extend their freshness and reduce spoilage. Extensive studies have been conducted to measure the shelf life of crops during cold storage by using different techniques, that control relative humidity. Evaporative cooling, air speed, and packaging used to store green pepper and compared with sustainability methods and non-packaging. The aim of the study was prolonging shelf life for at least seven days. The characteristics included weight loss (%), temperature (oC), relative humidity (%), and shelf-life (days). An air cooler with a volume of 2000 cu ft/s was used. An evaporative air cooler and the box are assemblage by a thermal insulating tube. The temperatures and humidity inside and outside the box were measured using the Arduino system using the DHT-22 temperature and humidity sensor. By measuring the percentage of weight loss and the storage period, evaporative cooling increased the green pepper’s shelf life by extending the crop’s life and reducing the percentage of weight loss when using evaporative cooling and packing. It was noted that there was a strong relationship between the decrease in the percentage of weight loss and packing.